Effect of Pre-transplant Skeletal Muscle Mass on Early Outcome of Allogeneic Hematopoietic Stem Cell Transplantation - WU Fangfang, DU Shanshan, DU Xin, XU Rufu, SUN Aihua, KONG Peiyan, GAO Lei, ZHANG Xi (Zhongguo quanke yixue, 2024)
Background Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is an effective treatment for hematopoietic malignancies. Malnutrition is a common complication and negatively affects prognosis. Muscle mass has been shown to reflect the nutritional status of patients earlier than blood biochemical parameters such as albumin. However, the influence of pre-transplantation skeletal muscle mass (SMM) on the complications associated with early transplantation remains unclear. Objective To investigate the effect of pre-transplant SMM on the early outcomes of allo-HSCT, provide a clinical basis for nutritional interventions and prognosis improvement. Methods A study was conducted with 77 leukemia patients who underwent allo-HSCT at the Medical Center of Hematology, Xinqiao Hospital of Army Medical University from January to October 2022. Bioelectrical impedance analysis was used to assess skeletal muscle mass. The patients were divided into the normal SMM group of 36 cases and low SMM group of 41 cases according to their SMM. Baseline data, including personal and clinical details, were collected. Early post-transplant complications (within 30 days post-transplant) such as oral mucositis, gastrointestinal symptoms, infection and hematopoietic reconstitution time between the two groups were compared using SPSS 23.0 software. Results There was no statistically significant difference in the incidence of diarrhea, nausea, vomiting, and abdominal pain/gastritis incidence between the normal and low SMM groups (P>0.05). The incidence of oral mucositis, hypoalbuminemia, overt gastrointestinal bleeding, and infection was lower in the normal SMM group than in the low SMM group (P<0.05). The severity of oral mucositis in patients in the normal SMM group was lower than that in the low SMM group (P<0.001). Neutrophil implantation time and platelet implantation time were longer in patients in the low SMM group than in the normal SMM group (P<0.01) . Conclusion The pre-transplant patients had a high incidence of low SMM. The low SMM before transplantation correlates with the occurrence of oral mucositis, hypoalbuminemia, overt gastrointestinal bleeding, and infections, as well as extended neutrophil and platelet engraftment time in the early transplantation period, and patients should be screened as early as possible prior to transplantation to boost SMM and improve early post-transplant outcomes.